2001
DOI: 10.1210/mend.15.11.0723
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Suppression of GnRH-Stimulated Rat LHβ Gene Transcription Occurs Through Sp1 Sites in the Distal GnRH-Responsive Promoter Region

Abstract: Steroids may regulate LH subunit gene transcription by modulating hypothalamic GnRH pulse patterns or by acting at the pituitary gonadotrope to alter promoter activity. We tested direct pituitary effects of the androgen dihydrotestosterone (DHT) to modulate the rat LHbeta promoter in transfected LbetaT2 clonal gonadotrope cells and in pituitaries of transgenic mice expressing LHbeta-luciferase. The LHbeta promoter (-617 to +44 bp)-luciferase construct was stimulated in LbetaT2 cells 7- to 10-fold by GnRH. Andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…Repression of the luteinizing hormone ␤ subunit gene involved protein-protein interactions between AR and SF-1 (13). In a separate study, AR-mediated repression of the luteinizing hormone ␤ subunit gene was also found to occur through protein-protein interactions with Sp1 and to a lesser degree Egr-1 (14).…”
Section: Androgen Receptor (Ar)mentioning
confidence: 89%
“…Repression of the luteinizing hormone ␤ subunit gene involved protein-protein interactions between AR and SF-1 (13). In a separate study, AR-mediated repression of the luteinizing hormone ␤ subunit gene was also found to occur through protein-protein interactions with Sp1 and to a lesser degree Egr-1 (14).…”
Section: Androgen Receptor (Ar)mentioning
confidence: 89%
“…Crosstalk between transcription factors and nuclear hormone receptors have previously been found to produce either positive (39,40,44) or negative (41,45) regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sp1 and NFY cooperatively interact to regulate multiple genes through NFY-GC-rich motifs, and both proteins also physically interact (6 -10). Sp1 also binds estrogen receptor ␣ (ER␣) 1 and other members of the nuclear receptor family of transcription factors (11)(12)(13)(14)(15)(16)(17)(18)(19), and research in our laboratory has focused on the molecular mechanisms of the ligand-dependent activation of ER␣/Sp1 in breast and endometrial cancer cell lines (20 -31). Promoter analysis studies in breast cancer cells have identified GC-rich sites required for hormone activation of several genes including E2F1, DNA polymerase ␣, cyclin D1, insulin-like growth factor-binding protein 4, retinoic acid receptor ␣1, cathepsin D, vascular endothelial growth factor, c-fos, heat shock protein 27, bcl-2, thymidylate synthase, and adenosine deaminase (20 -27, 29 -31).…”
mentioning
confidence: 99%